Access to Essential Contraception, Family Planning, and Safe Motherhood Services During COVID-19 Pandemic: Single Secondary Level Care Hospital Experience - Jayanta Kumar Biswas; Soumen Das Poddar; Ganesh Saravagi; Ajith Nilakantan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: During the COVID-19 pandemic, more precisely as a result of restrictions on movement and continuing altered perception of essential health care services, women’s health is disproportionately affected due to reduced access to services as per reports and statements made by different global and national level Government and non-government agencies. We aimed to evaluate the health care impacts related to contraception, family planning, and safe motherhood in an Indian Armed Forces secondary level care hospital during the COVID-19 pandemic.